Polymer blends, methods of making and use thereof, amphiphilic elastomers and hydrogels
Patent Information
- Application Number
- CN202510549985.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0023]鉴于上述问题等,本申请的目的之一是提供一种聚合物共混物、其制备方法和用途、模塑制品和3D打印制品的制备方法、两亲性弹性体和水凝胶的制备方法以及水凝胶的用途,旨在解决现有生物医学水凝胶在力学性能、光学透明度、含水量和生物相容性方面受限,制备方法复杂、成本高、难以规模化,同时还存在性能不匹配和可持续性问题的技术问题
[0052]图1示出了根据本申请实施例的弹性体和水凝胶的一般加工步骤;
Smart Images

Figure CN123004064A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a partially or fully crosslinkable polymer blend formulation.
[0002] More specifically, this disclosure describes thermoplastic polymer blends, elastomers and hydrogels prepared therefrom with tunable properties.
[0003] This invention has practical applications in biomedical devices, especially in contact lenses. Background Technology
[0004] Biomedical hydrogels have wide applications in ophthalmology and tissue engineering, providing various solutions for drug delivery, wound healing, and tissue regeneration. These hydrogels are important components of medical devices, meeting the critical requirements for efficacy and safety in various biomedical applications.
[0005] Hydrogels used in medical devices must possess several key properties to ensure their functionality and biocompatibility. These properties include: mechanical strength to withstand physiological stress; optical transparency to provide clear vision; and high water content to mimic natural tissue. Furthermore, they must have good air and water permeability to ensure adequate oxygenation and hydration; and biocompatibility (ideally with FDA approval) to minimize adverse reactions.
[0006] Commercially available soft contact lens materials are composed of flexible polymers such as poly(hydroxyethyl methacrylate) (pHEMA), polyvinylpyrrolidone (PVP), polymethyl methacrylate (PMMA), silicone, or copolymers thereof.
[0007] In another application area, soft tissue substitutes utilize synthetic polymer hydrogels, such as polyvinyl alcohol (PVA), as well as natural polymers, such as gelatin, collagen, or other polysaccharides.
[0008] Advanced methods for preparing biomedical hydrogels include copolymerization and 3D printing. These methods have several drawbacks, including complex / uncontrolled reactions, uneven cross-linking leading to performance degradation, high production costs, and long processing times. Toxic residues may be generated during synthesis and manufacturing, raising sustainability concerns.
[0009] Meanwhile, current biomedical hydrogels used in tissue engineering have several significant drawbacks that hinder their widespread application. Most importantly, the mismatch in modulus and water content between hydrogels and natural tissues impedes their integration and functional properties. Furthermore, most traditional single-component hydrogels lack the fracture toughness and tear strength required for load-bearing tissue alternatives such as tendons and cartilage, as well as the durability and elasticity after long-term use. Finally, the continuous and low-cost production of hydrogels remains a major challenge due to the complexity of current manufacturing processes and the need for consistent quality control.
[0010] Furthermore, current hydrogel enhancement strategies often sacrifice other properties, such as optical transparency, water content, or biosafety, making them unsuitable for a wide range of biomedical applications.
[0011] In light of these issues, there is an urgent need to develop biomedical hydrogels with balanced, tunable properties and versatile, scalable processing methods. These hydrogels should possess enhanced mechanical properties, optimal matching with the physical properties of ophthalmic lenses and / or soft tissues, and sustainable manufacturing processes that reduce costs.
[0012] Currently disclosed methods for preparing biomedical hydrogels for ophthalmic applications or implants mainly revolve around the copolymerization of different hydrophilic monomers / oligomers. Most of these monomers are hydrophilic, such as HEMA and vinylpyrrolidone (VP); meanwhile, hydrophobic rigid lenses, such as MMA-VP, may cause discomfort during prolonged wear due to their high modulus and low water content. US20210315807A1 discloses a hydrogel composition based on polyrotaxane and its hydrogel lens. US 3,786,034 discloses a rigid hydrophilic polyurethane material made from specific polyols and polyfunctional isocyanates. US2021 / 0369911 A1 discloses a crosslinkable hydrogel composition based on isocyanates and glycerol oligomers. However, the preparation of such gels requires multiple steps of synthesis and purification.
[0013] In recent years, silicone-based flexible lenses have been more widely used due to their high oxygen permeability. However, the hydrophobicity of silicone can cause corneal discomfort.
[0014] Several strategies have been devised to impart hydrophilic properties to hydrophobic silicone lenses. For example, US US9268064B2 discloses an amphiphilic siloxane-containing acrylamide containing PEG segments as hydrophilic blocks, whose outer layer swells through self-assembly when immersed in water. US9521842B2 discloses a PBO-PEO-PBO block copolymer for modifying hydrophobic ophthalmic lens surfaces. US9000065B2 discloses a method for preparing a polyurethane dry gel with PEG as the structural unit, but the reaction must be carried out under strictly anhydrous conditions. In another example, US20230382066A1 discloses a silicone hydrogel composition and lens containing hydrophilic monomer units. US11802182B2 discloses a silicone-based hydrogel containing up to five different repeating units.
[0015] While copolymerization can effectively modulate the properties of hydrophobic silicone, it requires precise control over the chemical reactions and composition. Furthermore, toxic monomer residues necessitate further post-processing. Meanwhile, silicone copolymers with hydrophilic coatings represent an alternative strategy. US10920102B2 discloses a crosslinked hydrophilic coating with positively charged nitrogen-containing butaneonium groups on a silicone lens. US10920102B2 proposes a silicone hydrogel lens with a crosslinked hydrophilic coating made from end-functionalized linear or multi-arm polyethylene glycol (PEG), such as PEG-NH2, HOOC-PEG-COOH, HS-PEG-SH, etc. These methods typically require chemical modification of the matrix material and additional chemical reactions between the matrix and coating materials. Moreover, precise control over coating parameters (thickness and uniformity) requires additional processing steps. In contrast, direct mixing of polymers minimizes chemical reactions and provides stable performance, which is crucial.
[0016] Extrusion is a highly scalable processing method used in the polymer and plastics industry. The powerful mixing forces generated by the shear forces of an extruder can efficiently prepare polymer formulations in seconds to minutes. The extruded samples can then be thermoformed, such as by injection molding or hot pressing, to quickly obtain the desired sample shape. Traditional hydrogel preparation is often limited to aqueous molding techniques that require water-soluble components. Hydrogel articles made by 3D printing methods can achieve customized complex shapes, but often lack scalability and efficiency.
[0017] In the field of plastics and elastomers, physical blending of pre-existing polymers is a simple and sustainable method. Blending of hydrophilic and hydrophobic polymers is an emerging research area in patent and non-patent literature. The advantages of hydrophilic / hydrophobic polymer blends include well-defined molecular structures and chain lengths, moderate swelling, and amphiphilicity. However, issues such as phase separation, mechanical instability, and opacity pose challenges to these materials in implant or ophthalmic applications. These problems can be addressed by enhancing the solubility of the polymers or the compatibility between them. Solubility often leads to high transparency, mechanical properties, and other synergistic properties. However, most polymers are immiscible with each other.
[0018] The insolubility between polymers stems from their high molecular weight (Mw) and van der Waals repulsion. Traditionally, compatibility has been achieved through the design of specific attractive forces, such as ionic bonds or strong dipole-dipole interactions, which typically requires the introduction of highly polar functional groups such as amides, carboxylates, and hydroxyl groups. However, such components may be sensitive to or incompatible with the physiological environment of tissues. Recent research indicates that, under medium molecular weight conditions, favorable mixing entropy mediated by weak interactions and chain entanglement can enhance polymer compatibility without relying on specific interactions.
[0019] Hydrophobic surfaces or areas can absorb lipids or proteins from the ocular surface environment and may adhere to the eye. Therefore, silicone hydrogel contact lenses typically require surface modification.
[0020] Polyethylene glycol (PEG) has become the gold standard material in the biomedical field due to its excellent biocompatibility, hydrophilicity, and antifouling properties. Although PEG is widely used in drug delivery and wound healing, PEG-based hydrogels are rarely used in durable, load-bearing biomedical devices. The main reasons include: 1) unrestricted swelling, typically reaching 20-30 times the original weight; and 2) modulus below 100 kPa, strength less than 50 kPa, and notched toughness less than 100 J / m. 2 3) It will degrade after several months in the buffer solution, resulting in unstable storage.
[0021] Hydrophobic surfaces or areas can absorb lipids or proteins from the ocular surface environment, potentially leading to infection or discomfort. Therefore, silicone hydrogel contact lenses often require surface modification. For example, US patents US6,099,122, US6,521,352, US6,623,747, US6,730,366, US6,734,321, US6,835,410, US6,923,978, and US9708087B2 disclose techniques for grafting hydrophilic coatings onto contact lenses with surface functional groups. These techniques are applicable to photografting or chemical grafting of hydrophilic polymers. These functional groups may be naturally present in the lens (derived from functionalized monomers) or introduced through plasma treatment, plasma-induced graft polymerization, the use of functionalized photoinitiators, covalent bonding of photoinitiators, photografting of functionalized monomers, or a combination of these methods.
[0022] In the ophthalmology field, PEG is currently used as a coating material for silicone contact lenses. US Patent 2006 / 0275342A1 discloses a multi-step synthetic method for preparing PEG- and poloxamer-based lenses. Although PEG-containing contact lens formulations have been reported, these formulations typically require copolymerization with low-hydrophilic polymers such as silicone to reduce their swelling properties. US Patent 9,000,065B2 discloses a polyurethane copolymer formulation containing PEG segments as a hydrophilic component and its hydrogel. Summary of the Invention
[0023] In view of the above-mentioned problems, one of the objectives of this application is to provide a polymer blend, its preparation method and use, a method for preparing molded articles and 3D printed articles, a method for preparing amphiphilic elastomers and hydrogels, and the use of hydrogels. The aim is to solve the technical problems of existing biomedical hydrogels, which are limited in mechanical properties, optical transparency, water content and biocompatibility, have complex preparation methods, high costs and difficulty in scaling up, and also have performance mismatch and sustainability issues.
[0024] To achieve the above objectives, according to an embodiment of the first aspect of this application, a polymer blend is provided, comprising the following precursors:
[0025] 10 wt.% to 95.0 wt.% of hydrophilic polymers;
[0026] 5.0 wt.% to 95.0 wt.% of hydrophobic polymers; and
[0027] 0.1 wt.% to 5 wt.% of initiator.
[0028] According to an embodiment of the second aspect of this application, a method for preparing a polymer blend according to the first aspect is provided. The method includes:
[0029] The polymer blend is formed by mixing a hydrophilic polymer, a hydrophobic polymer, and an initiator through solution processing, melt processing, or a combination thereof.
[0030] In the solution processing method, the hydrophilic polymer, the hydrophobic polymer, and the initiator are dissolved in a solvent selected from acetone, acetonitrile (ACN), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), glycerol, tetrahydrofuran (THF), dichloromethane (DCM), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), water, alcohols, dioxane, or any combination thereof; and
[0031] In the melt processing method, the hydrophilic polymer, the hydrophobic polymer, and the initiator are directly melt-blended in an extruder or mixer at a temperature of 80°C to 180°C, a rotation speed of 10 rpm to 200 rpm, and a time of 1 min to 20 min.
[0032] According to embodiments of the third aspect of this application, the use of polymer blends according to the first aspect in the preparation of molded articles, 3D printed articles, amphiphilic elastomers and hydrogels is provided.
[0033] According to an embodiment of the fourth aspect of this application, a method for preparing a molded article is provided, comprising:
[0034] The polymer blend obtained according to the preparation method provided in the second aspect is dried, and the dried polymer blend is pressed at a temperature of 60°C to 180°C, a pressure of 5 bar to 150 bar, a total compression time of 0.1 min to 10 min, and a degassing time of 0.2 min to 5 min.
[0035] Alternatively, the polymer blend obtained according to the preparation method described in the second aspect is injection molded at a temperature of 60°C to 250°C, with an injection pressure of 10 bar to 1000 bar, an injection time of 0.2 min to 1 min, a holding pressure of 5 bar to 500 bar, and a holding time of 0.2 min to 1 min.
[0036] According to an embodiment of the fifth aspect of this application, a method for preparing 3D printed articles from a polymer blend obtained according to the preparation method of the second aspect is provided, wherein:
[0037] The filament extruded from the extruder or mixer is further processed on an extrusion-based 3D printer (such as fused deposition modeling (FDM)); or,
[0038] The polymer blends obtained through solution processing are then processed using liquid resin-based methods, such as stereolithography (SLA) and digital light processing (DLP).
[0039] According to an embodiment of the sixth aspect of this application, a method for preparing an amphiphilic elastomer is provided, comprising:
[0040] The amphiphilic elastomer is obtained by curing the polymer blend according to the first aspect, or the polymer blend prepared by the method for preparing polymer blends according to the second aspect, or the 3D printed article prepared by the method for preparing 3D printed articles according to the fifth aspect, under ultraviolet light irradiation or heat treatment.
[0041] According to an embodiment of the seventh aspect of this application, a method for preparing a hydrogel is provided, comprising:
[0042] Provides an amphiphilic elastomer prepared according to the method for preparing amphiphilic elastomers according to the sixth aspect; and
[0043] The amphiphilic elastomer is swollen to obtain a hydrogel.
[0044] According to an embodiment of the eighth aspect of this application, the application of a hydrogel prepared according to the preparation method of the seventh aspect in an implant is provided.
[0045] According to an embodiment of the ninth aspect of this application, an application of a hydrogel prepared according to the preparation method of the seventh aspect is provided in ophthalmic applications.
[0046] According to an embodiment of the tenth aspect of this application, the use of a hydrogel prepared according to the preparation method of the seventh aspect in the preparation of a drug delivery device is provided.
[0047] The beneficial effects of the embodiments of this application can be summarized as follows:
[0048] The polymer blends provided in this application include a precursor comprising: 10 wt.% to 95.0 wt.% of a hydrophilic polymer; 5.0 wt.% to 95.0 wt.% of a hydrophobic polymer; and 0.1 wt.% to 5 wt.% of an initiator. The blends can be prepared by mixing the hydrophilic polymer, the hydrophobic polymer, and the initiator via solution processing, melt processing, or a combination thereof. This invention allows for the direct extrusion of existing polymers without the need for chemical synthesis. This method reduces costs, ensures environmental safety, and facilitates large-scale production.
[0049] Traditional multi-component tough hydrogels are typically opaque. In contrast, the hydrogel prepared by the method described in this application achieves compatibility at the nanoscale and exhibits optical transparency exceeding 96%. This superior optical transparency makes it particularly suitable for lens applications.
[0050] This hydrogel exhibits a wide range of tunable stiffness and strength. Its mechanical toughness and tear strength surpass those of previously reported comparable materials, and it possesses comparable or superior permeability and antifouling properties. These improvements enhance the hydrogel's lifespan and durability, enabling it to meet diverse stiffness and strength requirements, such as those needed for cartilage applications. Brief description of the attached figures
[0051] The embodiments of the present invention will now be described in more detail with reference to the accompanying drawings, wherein:
[0052] Figure 1 The general processing steps of the elastomers and hydrogels according to embodiments of this application are shown;
[0053] Figure 2 Hydrogels prepared according to the method of embodiments of this application at different PMMA mass ratios are shown. Oxygen permeability (Dk / t) at that point;
[0054] Figure 3 Hydrogels prepared according to the method of embodiments of this application at different PMMA mass ratios are shown. The results of the antifouling test were presented and compared with those of other specific materials in the prior art;
[0055] Figure 4 The visible light transmittance results of the hydrogel prepared according to the method of embodiments of this application are shown;
[0056] Figure 5 Hydrogels prepared according to the method of embodiments of this application at different PMMA mass ratios are shown. The following are the cytotoxic results;
[0057] Figure 6 Hydrogels prepared according to the method of embodiments of this application at different PMMA mass ratios are shown. Mechanical properties under these conditions; and
[0058] Figure 7 Hydrogels prepared according to the method of embodiments of this application at different PMMA mass ratios are shown. Mechanical properties under [condition]. Specific Implementation
[0059] To further illustrate the present invention, the following describes in detail, through experiments, a polymer blend, its preparation method and uses, a method for preparing molded articles and 3D printed articles, a method for preparing amphiphilic elastomers and hydrogels, and the uses of hydrogels. It should be noted that the following examples are for illustrative purposes only and are not intended to limit the scope of the invention.
[0060] On one hand, embodiments of this application provide a polymer blend comprising the following precursors:
[0061] 10 wt.% to 95.0 wt.% of hydrophilic polymers;
[0062] 5.0 wt.% to 95.0 wt.% of hydrophobic polymers; and
[0063] 0.1 wt.% to 5 wt.% of initiator.
[0064] In one embodiment, the precursor further comprises 0.01 wt.% to 5 wt.% of a crosslinking agent.
[0065] In one embodiment, the precursor further comprises a solvent, wherein the concentration of the solute is from 1 wt.% to 80 wt.%.
[0066] In one embodiment, the precursor further comprises a plasticizer.
[0067] In one embodiment, the content of the hydrophilic polymer is from 33 wt.% to 67 wt.%.
[0068] In one embodiment, the content of the hydrophobic polymer is from 33 wt.% to 67 wt.%.
[0069] In one embodiment, the initiator content is from 1 wt.% to 5 wt.%.
[0070] In one embodiment, the solvent content satisfies the requirement that the concentration of solute in the solvent is between 10 wt.% and 50 wt.%.
[0071] In one embodiment, the hydrophilic polymer is at least one of the following: polyethylene glycol or polyvinyl alcohol; a block copolymer of polyethylene oxide (PEO) and polypropylene oxide (PPO), selected from... F108, F127, or P123; or synthetic polymers or oligomers of polyacrylic acid (PAAc), polyacrylamide (PAAm), polyhydroxyethyl methacrylate (HEMA), or copolymers thereof, wherein the molecular weight of the hydrophilic polymer is between 200 Da and 6000 Da. In one embodiment, when the hydrophilic polymer is a synthetic polymer or oligomer of polyacrylic acid (PAAc), polyacrylamide (PAAm), polyhydroxyethyl methacrylate (HEMA), or copolymers thereof, and the molecular weight of the hydrophilic polymer is between 200 Da and 6000 Da, a crosslinking agent may be used.
[0072] In one embodiment, the hydrophilic polymer includes a polymer or copolymer of ethylene glycol.
[0073] In alternative embodiments, the hydrophilic polymer may also be a nonionic polymer, such as pHEMA, PAAm, PVA, or an ionic polymer, such as polyacrylic acid (PAAc), as well as mixtures or copolymers thereof in appropriate proportions.
[0074] In one embodiment, the hydrophobic polymer is selected from polystyrene (PS), polycarbonate (PC), polymethyl methacrylate (PMMA), polylactic acid (PLA), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS), polyvinylidene fluoride (PVDF), and polyethylene naphthalate (PEN); and the molecular weight of the hydrophobic polymer is between 10 kDa and 100 kDa.
[0075] In a preferred embodiment, the hydrophobic component may be a biocompatible glassy thermoplastic, such as PMMA, polystyrene (PS), or polylactic acid (PLA). In another embodiment, a rubbery polymer may be used, such as styrene-butadiene-styrene copolymer (SBS), thermoplastic polyurethane (TPU), and polyolefin elastomer (POE).
[0076] In a preferred embodiment, the hydrophilic polymer is polyethylene glycol or polyvinyl alcohol; the hydrophobic polymer is polymethyl methacrylate or polylactic acid; and the initiator is benzophenone or an amine compound.
[0077] In one embodiment, the solvent is selected from acetone, acetonitrile (ACN), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), glycerol, tetrahydrofuran (THF), dichloromethane (DCM), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), water, alcohols, dioxane, or any combination thereof. Mixed solvent systems can be used to enhance solubility.
[0078] In one embodiment, the solvent may be a protic or aprotic polar organic substance, such as water, alcohols, acetone, tetrahydrofuran, dioxane, dimethyl sulfoxide (DMSO), or mixtures thereof.
[0079] In one embodiment, the crosslinking agent is selected from glutaraldehyde, ethylene glycol dimethacrylate (EGDMA), N,N'-methylenebisacrylamide (MBAA), 1,4-butanediol diacrylate (BDDA), polyethylene glycol diacrylate (PEGDA), divinyl sulfone (DVS), hexamethylene diisocyanate (HMDI), diethylene glycol dimethacrylate (DEGDMA), N,N'-disacryloylpiperazine (DAP), or polyethylene glycol dimethacrylate (PEGDMA).
[0080] The chemical structural formula of polyethylene glycol is formula (1):
[0081]
[0082] The chemical structural formula of polyvinyl alcohol is formula (2):
[0083]
[0084] The chemical structural formula of polymethyl methacrylate is formula (3):
[0085]
[0086] The chemical structural formula of poly(D,L-lactide) is:
[0087]
[0088] The chemical structural formula of the benzophenone initiator is:
[0089]
[0090] The general chemical formula for poloxamer is: HO(C2H4O) x (C3H6O) y (C2H4O) x H, where x and y have different lengths.
[0091] The general chemical structural formula of poloxamer is: HO(C3H6O). x (C2H4O) y (C3H6O) x H, where the lengths of x and y are different.
[0092] Secondly, one embodiment of this application provides a method for preparing the polymer blend described in the first aspect. The preparation method includes:
[0093] The polymer blend is formed by mixing a hydrophilic polymer, a hydrophobic polymer, and an initiator through solution processing, melt processing, or a combination thereof.
[0094] In one specific embodiment, in the solution processing method, the hydrophilic polymer, the hydrophobic polymer, and the initiator are dissolved in a solvent selected from acetone, acetonitrile (ACN), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), glycerol, tetrahydrofuran (THF), dichloromethane (DCM), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), water, alcohols, dioxane, or any combination thereof.
[0095] In one embodiment, during the melt processing method, the precursor of the polymer blend is directly melt-blended in an extruder or mixer. Preferably, during the melt processing method, the precursor of the polymer blend is added together with a plasticizer into the extruder or mixer and mixed at a temperature of 80°C to 180°C, a rotation speed of 10 rpm to 200 rpm, and a time of 1 min to 20 min. It is understood that the extruder can be a single-screw extruder or a twin-screw extruder, and the mixer can be a Banbury mixer or other similar mixing equipment.
[0096] In a preferred embodiment, for the solution processing method, the two polymers are PEG and PMMA, the solvent is acetone, the solution concentration is 20 wt.% to 50 wt.%, the PEG:PMMA ratio is 9:1, and the solvent is fully evaporated overnight under vacuum conditions.
[0097] In a preferred embodiment, for melt processing, the equipment temperature is 80°C to 180°C, the sample residence time is 1 min to 15 min, the rotor speed is 30-150 rpm, and nitrogen purging can be used for protection. An inert gas (e.g., nitrogen / argon) is introduced into the system to protect the polymer blend.
[0098] Preferably, PEG with a molecular weight of 10-1000 kDa is used. More preferably, for solution processing, PEG with a molecular weight of less than 35 kDa is used; for melt processing, PEG with a molecular weight of 35-1000 kDa is used. When the molecular weight is low (less than 35 kDa), the blend is mostly transparent. When the molecular weight is high, the lens becomes more transparent.
[0099] Preferably, PMMA with a molecular weight of 30 kDa to 1000 kDa is used. More preferably, for solution processing, PMMA with Mn = <350 kDa is used; for melt processing, PMMA with Mw = 35-1000 kDa is used.
[0100] In a preferred embodiment, the precursor may include: polyethylene glycol (PEG, Mw = 10 kDa–100 kDa), polymethyl methacrylate (PMMA, Mn = 50 kDa–350 kDa), and benzophenone (BP, 99%, Alfa Aesar). In a solution method, 20% to 83.3% of PEG, 16.7% to 80% of PMMA, and 0.1% to 5% of BP are co-dissolved in acetone or THF at a concentration of 1% to 80% under vigorous stirring at a temperature of 40°C to 55°C, followed by ultrasonic degassing for 1 min or standing for 15 min. The solution can then be cast and vacuum-sealed, or dried in a rotary evaporator to recover the solvent.
[0101] In extrusion-based methods, polyethylene oxide (PEO) with a molecular weight (Mw) between 35 kDa and 1,000 kDa can be added as a plasticizer. The aforementioned precursor with added plasticizer is mixed in a mixer and extruder at 80-180°C and 30-200 rpm.
[0102] In one embodiment, following solution processing or melt processing, the preparation method further includes thermoforming the polymer blend to form a film or an ASTM standard specimen. The thermoforming can be performed using hot pressing or injection molding. The thickness of the film or ASTM standard specimen can be between 0.01 mm and 1 mm.
[0103] Dry elastomers typically have a modulus of 0.1 GPa to 3 GPa, a tensile strength of 2 MPa to 20 MPa, exhibit rubber behavior, and an elongation at break of 200% to 1000%.
[0104] According to embodiments of the third aspect of this application, the use of polymer blends according to the first aspect in the preparation of molded articles, 3D printed articles, amphiphilic elastomers and hydrogels is provided.
[0105] According to an embodiment of the fourth aspect of this application, a method for preparing a molded article is provided, comprising:
[0106] The polymer blend obtained by the preparation method provided in the second aspect is dried, and the dried polymer blend is pressed at a temperature of 60-180°C, a pressure of 5-150 bar, a total compression time of 0.1-10 min, and a degassing time of 0.2-5 min.
[0107] Alternatively, the polymer blend obtained according to the preparation method described in the second aspect is injection molded at a temperature of 60°C to 250°C, with an injection pressure of 10 bar to 1000 bar, an injection time of 0.2 min to 1 min, a holding pressure of 5 bar to 500 bar, and a holding pressure time of 0.2 min to 1 min.
[0108] According to an embodiment of the fifth aspect of this application, a method for preparing 3D printed articles from polymer blends obtained according to the preparation method of the second aspect is provided. Filaments extruded from an extruder or mixer are further processed on an extrusion-based 3D printer, such as fused deposition modeling (FDM); or, polymer blends obtained by solution processing are molded using liquid resin-based methods, such as stereolithography (SLA) and digital light processing (DLP).
[0109] According to an embodiment of the sixth aspect of this application, a method for preparing an amphiphilic elastomer is provided, comprising: curing a polymer blend according to the first aspect, or a polymer blend prepared by the method for preparing a polymer blend according to the second aspect, or a 3D printed article prepared by the method for preparing a 3D printed article according to the fifth aspect, under ultraviolet light irradiation or heat treatment to obtain the amphiphilic elastomer.
[0110] In one embodiment, the curing step includes: irradiating the polymer blend with ultraviolet light, for example, for an irradiation time between 0.1 hours and 1 hour, at a power density of 1 mW / cm². 2 Up to 500mW / cm 2 The irradiation time depends on the sample thickness, initiator type, and concentration.
[0111] According to an embodiment of the seventh aspect of this application, a method for preparing a hydrogel is provided, comprising:
[0112] Provides an amphiphilic elastomer prepared according to the method for preparing amphiphilic elastomers according to the sixth aspect; and
[0113] The amphiphilic elastomer is swollen to obtain a hydrogel.
[0114] In one embodiment, after thermoforming, the dry blend is irradiated with ultraviolet light (1-100 mW / cm²). 2 Cross-linked and swollen in water / simulated body fluid to form a blended hydrogel.
[0115] In one embodiment, the swelling step includes immersing the amphiphilic elastomer formed under ultraviolet light irradiation in a standard salt solution for at least 24 hours, or in deionized water or phosphate buffer solution for at least 2 hours.
[0116] For contact lens applications, a hydrogel film with a thickness of 0.01-0.1 mm is preferred. For mechanical testing and implant applications, statistically effective thickness measurements are performed using samples with a thickness of 0.5-1 mm.
[0117] In one variant, the hydrophilic component can be an oligomer with UV-crosslinkable end groups, such as PEG / gelatin diacrylate or methacrylate.
[0118] In another variant, the hydrophobic component can be an existing copolymer, such as MMA / HEMA, MMA / VP, styrene-acrylonitrile (SAN), or ethylene-vinyl acetate copolymer (EVA).
[0119] Depending on the composition, the Young's modulus of the blended hydrogels can be adjusted within four orders of magnitude, ranging from ~10⁻² MPa to ~10² MPa; the tensile strength can be adjusted between 0.02 and 20 MPa; the elongation at break of all samples is greater than 200%, typically between 300 and 500%; and the fracture toughness is 1–20 kJ / m. 2 .
[0120] Hydrogels typically contain 30–80% water, have a transmittance of 96.2–98.1% in the visible light range (500 nm) (0.1 mm thickness), and a tear strength of 2–25 g / mm.
[0121] The oxygen permeability (Dk / t) of the hydrogel can reach 40-103 barrer / mm. (ISO18369-4)
[0122] According to an embodiment of the eighth aspect of this application, the use of a hydrogel prepared by the preparation method described in the seventh aspect in an implant application is provided.
[0123] For implant applications, the hydrogel has a water content of 60-80% and a fracture toughness G > 1 kJ / m. 2 (Single-sided notch tensile test) showed good biocompatibility in cytotoxicity test (cell viability >96%).
[0124] According to an embodiment of the ninth aspect of this application, the use of a hydrogel prepared by the preparation method described in the seventh aspect in ophthalmic applications is provided.
[0125] For ophthalmic applications, the blended hydrogels have a water content of 30-80%, a refractive index of 1.35-1.39, and a tensile strength of 0.1-10 MPa. They retain over 95% of their original mechanical properties after 180 days of storage in buffer solutions. At higher PEG contents, the blended hydrogels also exhibit antifouling properties due to the hydration layer formed by the hydrophilic PEG. After 72 hours of incubation, the albumin concentration deposited on the gel surface is 0.38-0.55 μg / cm³. 2 .
[0126] It is also understandable that blended hydrogels can be used for large-scale production. For large-scale production, blended hydrogels require no solvents or processing agents. Due to the inherent compatibility between polymers, uniform mixing can be achieved through extrusion in a short time. All raw materials require minimal pretreatment or chemical modification, thus reducing costs. Compared to traditional monomer solution preparation of hydrogel materials, this method is environmentally friendly, simple, and inexpensive. For solution blending, low-boiling-point solvents (such as acetone and tetrahydrofuran) can be recovered via vacuum distillation near room temperature. This method is also suitable for low to medium molecular weight ranges.
[0127] According to an embodiment of the tenth aspect of this application, a hydrogel prepared by the preparation method of the seventh aspect is provided for use in the preparation of a drug delivery device.
[0128] In one embodiment, the polymer blend is mixed, molded, or 3D printed into the desired shape, and the cured elastomer is immersed in a drug solution.
[0129] This document will describe in detail some embodiments of the present disclosure. However, the present disclosure is not limited to these embodiments. Example Example 1: Preparation of polymer blends Example 1.1
[0130] PEG with a molecular weight of 35 kDa, PMMA with a molecular weight of 70 kDa, and benzophenone (BP, 99%, AlfaAesar) are provided as precursors.
[0131] The aforementioned precursors were co-blended using a solution method. Specifically, a total of 3g of polymer (containing 20wt.% PEG, 80wt.% PMMA, and 1wt.% BP by mass) was co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 50°C until the precursor concentration reached 30%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0132] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3Cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.2
[0133] PEG with a molecular weight of 35 kDa, PMMA with a molecular weight of 70 kDa, and benzophenone (BP, 99%, AlfaAesar) are provided as precursors.
[0134] The aforementioned precursors were solution blended. Specifically, a total of 3g of polymer (containing 25wt.% PEG and 75wt.% PMMA) and 0.5wt.% BP were co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 45°C until the precursor concentration reached 10%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0135] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3 Cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.3
[0136] PEG with a molecular weight of 10 kDa, PMMA with a molecular weight of 50 kDa, and benzophenone (BP, 99%, AlfaAesar) are provided as precursors.
[0137] The aforementioned precursors were solution blended. Specifically, a total of 3g of polymer (containing 33.3 wt.% PEG and 66.7 wt.% PMMA) and 2 wt.% BP were dissolved in a certain amount of acetone. The mixture was vigorously stirred at 50°C until the precursor concentration reached 10%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0138] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3 The sample is then cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.4
[0139] PEG with a molecular weight of 10 kDa, PMMA with a molecular weight of 50 kDa, and benzophenone (BP, 99%, AlfaAesar) are provided as precursors.
[0140] The aforementioned precursors were co-blended using a solution method. Specifically, a total of 3g of polymer (containing PEG and PMMA in a mass ratio of 50wt.% and BP in a mass ratio of 50wt.% and BP in a mass ratio of 0.5wt.%) was co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 55°C until the mass concentration of the precursor reached 10%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0141] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3 Cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.5
[0142] PEG with a molecular weight of 20 kDa, PMMA with a molecular weight of 120 kDa, and benzophenone (BP, 99%, AlfaAesar) were provided as precursors.
[0143] The aforementioned precursors were solution blended. Specifically, a total of 3g of polymer (containing 66.7wt.% PEG and 33.3wt.% PMMA) and 2wt.% BP of the total polymer mass were co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 50°C to achieve a precursor concentration of 20%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0144] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3 Cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.6
[0145] PEG with a molecular weight of 20 kDa, PMMA with a molecular weight of 120 kDa, and benzophenone (BP, 99%, AlfaAesar) were provided as precursors.
[0146] The aforementioned precursors were solution blended. Specifically, a total of 3g of polymer (containing 75wt.% PEG and 25wt.% PMMA) and 0.75wt.% BP were co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 50°C until the precursor concentration reached 20%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0147] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3Cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.7
[0148] PEG with a molecular weight of 35 kDa, PMMA with a molecular weight of 350 kDa, and benzophenone (BP, 99%, AlfaAesar) are provided as precursors.
[0149] The aforementioned precursors were co-blended using a solution method. Specifically, a total of 3g of polymer (containing 80wt.% PEG, 20wt.% PMMA, and 5wt.% BP by mass) was co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 50°C until the precursor concentration reached 40%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuumed to recover the solvent.
[0150] The resulting polymer blend sample was pressurized at 1 MPa and 70 °C, and then subjected to a 100 mW / cm² pressure. 3 Cured under ultraviolet light for 10 minutes to form an elastomer sample with dimensions conforming to ASTM standards. Example 1.8
[0151] PEG with a molecular weight of 35 kDa, PMMA with a molecular weight of 350 kDa, and benzophenone (BP, 99%, AlfaAesar) were provided as precursors.
[0152] The aforementioned precursors were co-blended using a solution method. Specifically, a total of 3g of polymer (containing 83.5 wt.% PEG, 16.7 wt.% PMMA, and 2 wt.% BP by mass) was co-dissolved in a certain amount of acetone. The mixture was vigorously stirred at 50°C until the precursor concentration reached 40%, followed by ultrasonic degassing for 1 min. The solution was then cast and vacuum-sealed to recover the solvent.
[0153] The obtained polymer blend samples were molded at 1 MPa and 70 °C, and then subjected to a pressure of 100 mW / cm. 3 After curing under ultraviolet light for 10 minutes, an elastomer sample with dimensions conforming to ASTM standards was obtained. Example 2: Preparation of hydrogels
[0154] The molded elastomer samples prepared in Examples 1.1 to 1.8 were respectively cured in a commercial UV curing chamber (λ = 365-385 nm, I = 1-100 mW / cm²). 2 It is cured in )
[0155] The elastomer film is then immersed in phosphate buffer for 2 hours. The typical hydration time is 12 hours, until the hydration degree reaches less than 1% and the equilibrium water content (EWC) stabilizes, thus obtaining the hydrogel.
[0156] EWC is calculated as follows: Where mw represents the mass of water and mw represents the mass of solids. Example 3: Characterization and Performance Studies
[0157] Tensile testing. Uniaxial tension was applied to the material at a constant strain rate using an Instron 5969 tensile testing machine to determine modulus, strength, elongation, and notched toughness. Hydrogels were tested under humid conditions with relative humidity >90%.
[0158] Before testing, samples were stored in phosphate-buffered saline at 20-25°C for at least 48 hours, in accordance with ISO 18369-3:2017.
[0159] The oxygen permeability (Dk / t) of the gel membrane was determined using online mass spectrometry. Measurements were performed using a benchtop residual gas mass spectrometer (Hiden Analytical, HPR-20TMS model) based on a modified test protocol according to ISO 18369-4. The measurements were performed for different PMMA mass ratios listed in Table 1. The test results are as follows Figure 2 As shown.
[0160] Antifouling tests or protein adsorption were evaluated using PBS artificial tears containing bovine serum albumin (BSA, Sigma Aldrich). In a typical procedure, the prepared hydrogel was perforated using a film cutter to create standard-sized gel membranes (d = 16 mm, t = 100 ± 20 μm). The membranes were then washed in pure PBS and equilibrated for 24 hours, followed by incubation in a BSA solution (1 mg / mL) at pH 7.4 for 72 hours. After three cycles of PBS washing to remove loosely bound albumin, the adsorbed protein was recovered with 200 μL of 1% sodium dodecyl sulfate (SDS). Pierce was used. TM BCA is used to determine the amount of protein absorbed. This is based on the different PMMA mass ratios listed in Table 1. And, as a comparison, specific materials in the prior art, the test results are as follows: Figure 3 As shown. The concentrations of each protein solution were calculated after background correction.
[0161] The wet samples were subjected to UV-Vis spectral analysis using a UV-1900 instrument, with a wavelength range of 200-800 nm. Visible light transmittance values were measured at a wavelength of 500 nm (Table 2). Figure 4 ).
[0162] Young's modulus is determined by the slope at 1% strain.
[0163] Within the test range, increasing the strain rate leads to an increase in modulus and tensile strength, but has no significant effect on elongation at break.
[0164] Material toughness G is measured by a single-sided notch test, in J / m. 2 Units: G=πσ 2 a / E[1.122-0.231(a / b)+10.55(a / b) 2 -21.71(a / b) 3 +30.382(a / b) 4 ] 2 , Table 1. Physical properties of the elastomers prepared in Examples 1.1 to 1.8 and the hydrogels prepared in Example 2. Table 2 Comparison of the physical properties of hydrogels with those in patent literature
[0165] The beneficial effects of the embodiments of this application can be summarized as follows:
[0166] The polymer blends provided in this application include, as a precursor, 10 wt.% to 95.0 wt.% of a hydrophilic polymer, 5.0 wt.% to 95.0 wt.% of a hydrophobic polymer, and 0.1 wt.% to 5 wt.% of an initiator. The blends can be prepared by mixing the hydrophilic polymer, the hydrophobic polymer, and the initiator via solution processing, melt processing, or a combination thereof. This invention allows for the direct extrusion of existing polymers without the need for chemical synthesis. This method reduces costs, ensures environmental safety, and facilitates large-scale production.
[0167] Traditional multi-component tough hydrogels are typically opaque. In contrast, the hydrogel prepared by the method described in this application achieves compatibility at the nanoscale and exhibits optical transparency exceeding 94%. This superior optical transparency makes it particularly suitable for lens applications.
[0168] Table 1 Figure 6 and Figure 7These hydrogels exhibit some typical mechanical properties. They possess a wide range of tunable stiffness and strength. Their mechanical toughness and tear strength exceed those of previously reported comparable materials, while exhibiting comparable or superior permeability and antifouling properties. These improvements enhance the service life and durability of the hydrogels, enabling them to meet various stiffness and strength requirements, such as those required for cartilage applications.
[0169] Unless otherwise stated, all numerical ranges involved in this invention include end values. While specific embodiments of the invention have been shown and described, those skilled in the art will understand that various changes and modifications can be made without departing from the broader aspects of the invention. Therefore, the appended claims are intended to cover all such changes and modifications, provided they fall within the true spirit and scope of the invention.
[0170] While the invention has been explained and described in detail in the accompanying drawings and the foregoing description, these explanations and descriptions should be considered illustrative or exemplary, not restrictive. It should be understood that various changes and modifications can be made by those skilled in the art within the scope of the following claims. Specifically, the invention covers further embodiments having any combination of features from the various embodiments described. Furthermore, statements characterizing the invention herein refer to one embodiment of the invention, and not necessarily all embodiments.
[0171] The terminology used in the claims should be understood to have the broadest and most reasonable interpretation consistent with the foregoing description. For example, the use of the articles “a” or “the” when introducing an element should not be construed as excluding multiple elements. Similarly, the expression “or” should be construed as including multiple elements; for example, the expression “A or B” does not exclude “A and B” unless the context or the foregoing description explicitly indicates that it refers to only one of A and B. Furthermore, the expression “at least one of A, B, and C” should be construed as one or more of the group of elements consisting of A, B, and C, and should not be construed as requiring at least one of each of the listed elements A, B, and C, regardless of whether A, B, and C belong to the same category. In addition, the expressions “A, B, and / or C” or “at least one of A, B, or C” should be understood to include any single entity of the listed elements, such as A, any subset of the listed elements, such as A and B, or the complete list of elements A, B, and C.
[0172] Unless otherwise stated, the terms “comprising,” “having,” “including,” and “containing” should be understood as open-ended terms (i.e., meaning “including but not limited to”). Unless otherwise stated herein, the expressions of numerical ranges herein are intended only as a shorthand method to refer to each individual value within a range separately, and each individual value is incorporated into the specification as if it were individually stated herein. Unless otherwise stated herein or clearly contradicted by the context, all methods described herein may be performed in any suitable order. Any and all examples or exemplary wording provided herein (e.g., “for example”) are intended only to better illustrate the invention and, unless otherwise stated, do not constitute a limitation on the scope of the invention. No wording in this specification should be construed as indicating that any unstated element is essential for the practice of the invention.
Claims
1. A polymer blend comprising the following precursors: 10 wt.% to 95.0 wt.% of hydrophilic polymers; 5.0 wt.% to 95.0 wt.% of hydrophobic polymers; and 0.1 wt.% to 5 wt.% of initiator.
2. The polymer blend according to claim 1, wherein, The precursor also includes: 0.01 wt.% to 5 wt.% crosslinking agent; and / or Solvent, wherein the concentration of solute is from 1 wt.% to 80 wt.%; and / or Plasticizer.
3. The polymer blend according to claim 2, wherein... The content of the hydrophilic polymer is from 33 wt.% to 67 wt.%; and / or The content of the hydrophobic polymer is from 33 wt.% to 67 wt.%; and / or The content of the hydrophobic initiator is from 1 wt.% to 5 wt.%; and / or The solvent content satisfies the requirement that the concentration of the solute in the solvent is between 10 wt.% and 50 wt.%.
4. The polymer blend according to claim 2, wherein, The solvent is selected from acetone, acetonitrile (ACN), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), glycerol, tetrahydrofuran (THF), dichloromethane (DCM), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), water, alcohols, dioxane, or any combination thereof.
5. The polymer blend according to claim 1, wherein, The hydrophilic polymer is at least one of the following: Polyethylene glycol or polyvinyl alcohol; A block copolymer of polyethylene oxide (PEO) and polypropylene oxide (PPO), selected from... F108, F127, or P123; or Synthetic polymers or oligomers of polyacrylic acid (PAAc), polyacrylamide (PAAm), hydroxyethyl methacrylate (HEMA) or their copolymers, wherein the molecular weight of the hydrophilic polymer is between 200 Da and 6000 Da.
6. The polymer blend according to claim 1, wherein... The hydrophobic polymer is selected from polystyrene (PS), polycarbonate (PC), polymethyl methacrylate (PMMA), polylactic acid (PLA), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS), polyvinylidene fluoride (PVDF), and polyethylene naphthalate (PEN); and The molecular weight of the hydrophobic polymer is between 10 kDa and 100 kDa.
7. The polymer blend according to claim 1, wherein... The hydrophilic polymer is polyethylene glycol or polyvinyl alcohol; The hydrophobic polymer is polymethyl methacrylate or polylactic acid; The initiator is benzophenone or an amine compound.
8. The polymer blend according to claim 2, wherein the crosslinking agent is selected from glutaraldehyde, ethylene glycol dimethacrylate (EGDMA), N,N'-methylenebisacrylamide (MBAA), 1,4-butanediol diacrylate (BDDA), polyethylene glycol diacrylate (PEGDA), divinyl sulfone (DVS), hexamethylene diisocyanate (HMDI), diethylene glycol dimethacrylate (DEGDMA), N,N'-disacryloylpiperazine (DAP), or polyethylene glycol dimethacrylate (PEGDMA).
9. A method for preparing a polymer blend according to any one of claims 1-8, comprising: The polymer blend is formed by mixing a hydrophilic polymer, a hydrophobic polymer, and an initiator through solution processing, melt processing, or a combination thereof. In the solution processing method, the hydrophilic polymer, the hydrophobic polymer, and the initiator are dissolved in a solvent selected from acetone, acetonitrile (ACN), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), glycerol, tetrahydrofuran (THF), dichloromethane (DCM), dimethylacetamide (DMAc), methyl ethyl ketone (MEK), water, alcohols, dioxane, or any combination thereof; and In the melt processing method, the hydrophilic polymer, the hydrophobic polymer, and the initiator are directly melt-blended in an extruder or mixer at a temperature of 80°C to 180°C, a rotation speed of 10 rpm to 200 rpm, and a time of 1 min to 20 min.
10. The method for preparing the polymer blend according to claim 9, further comprising: The polymer blend is thermoformed to form a film or an ASTM standard specimen.
11. Use of the polymer blends according to any one of claims 1-8 in the preparation of molded articles, 3D printed articles, amphiphilic elastomers and hydrogels.
12. A method for preparing a molded article, comprising: The polymer blend obtained by the preparation method according to claim 9 is dried, and the dried polymer blend is pressed at a temperature of 60°C to 180°C, a pressure of 5 bar to 150 bar, a total compression time of 0.1 min to 10 min, and a degassing time of 0.2 min to 5 min. Alternatively, the polymer blend obtained by the preparation method according to claim 9 is injection molded at a temperature of 60°C to 250°C, with an injection pressure of 10 bar to 1000 bar, an injection time of 0.2 min to 1 min, a holding pressure of 5 bar to 500 bar, and a holding time of 0.2 min to 1 min.
13. A method for preparing 3D printed articles from polymer blends obtained by the preparation method according to claim 9, comprising: Filaments extruded from an extruder or mixer are processed on an extrusion-based 3D printer; or, The polymer blends obtained by the solution processing method are processed using a liquid resin-based method.
14. A method for preparing an amphiphilic elastomer, comprising: The amphiphilic elastomer is obtained by curing the polymer blends according to any one of claims 1-8, or the polymer blends prepared by the method of preparing the polymer blends according to any one of claims 9-10, or the 3D printed articles prepared by the method of preparing 3D printed articles according to claim 13, under ultraviolet light irradiation or heat treatment.
15. The method for preparing the amphiphilic elastomer according to claim 14, wherein the curing step comprises: The polymer blend was irradiated with ultraviolet light.
16. A method for preparing a hydrogel, comprising: Provides an amphiphilic elastomer prepared by the method for preparing the amphiphilic elastomer according to any one of claims 14-15; as well as The amphiphilic elastomer is swollen to obtain a hydrogel.
17. The preparation method according to claim 16, wherein, The swelling step includes immersing the amphiphilic elastomer formed by ultraviolet light irradiation in a standard physiological saline solution for at least 24 hours, or immersing it in deionized water or phosphate buffer for at least 2 hours.
18. Use of the hydrogel prepared by the preparation method according to any one of claims 16-17 in implant applications.
19. Use of the hydrogel prepared by the preparation method according to any one of claims 16-17 in ophthalmic applications.
20. Use of the hydrogel prepared by the preparation method according to any one of claims 16-17 in the preparation of a drug delivery device.
21. The use according to claim 20, wherein, The polymer blend is mixed, molded, or 3D printed into the desired shape, and the cured elastomer is immersed in a drug solution.
Citation Information
Patent Citations
Silicone hydrogel lens with a crosslinked hydrophilic coating
US10920102B2
Silicone hydrogel contact lenses
US11802182B2
Polymerizable surfactants and their use as device forming comonomers
US20060275342A1
Hydrogel composition and hydrogel lens
US20210315807A1
Hydrogel compositions
US20210369911A1
